THE DIFFERENCES BETWEEN PERIMETER AND POST BASKETBALL PLAYERS IN SOME AEROBIC AND ANAEROBIC PARAMETERS - Samir Mačković; Haris Pojskić; Edin Užičanin (Sport Scientific And Practical Aspects, 2025)
The aim of this study was to find out the differences between perimeter and post basketball players in aerobic and anaerobic parameters. Thirty-four basketball players from four Bosnian teams were measured for body composition (body height and weight, fat%, fat free mass), aerobic power (VO2max prediction estimated using the multistage shuttle run test), anaerobic capacities (repeated anaerobic sprint test – RAST) and anaerobic power (peak and relative power output generated during the CMJ). The sample was divided in two sub-samples: the first was a group of perimeter basketball players (n = 17) and the second was a group of post players (n =17). The main finding of this research was the existence of differences between the perimeter and post basketball players in aerobic power and relative anaerobic parameters, but not in vertical jump height. The perimeter players had higher aerobic power and higher values of relative anaerobic power and capacities, while the post players have higher values of absolute anaerobic power. The findings confirm that the aerobic and anaerobic tests can be discriminative variables between perimeter and post basketball players. Additionally, the results emphasize the need for improvement of explosive power of the lower limbs in Bosnian players. Also, the coaches can use information obtained in the study to create more individualized strength and conditioning programs for different positional role in order to maximize players’ physiological potential which is very important for basketball to be successfully played.